MRNA abundance changes during in vitro oocyte ageing in African catfish Clarias gariepinus (Burchell, 1822). (7th December 2017) - Samarin, Azadeh Mohagheghi; Sampels, Sabine; Policar, Tomas; Rodina, Marek; Hematyar, Nima; Samarin, Azin Mohagheghi
Abstract: Delayed fertilization following ovulation leads to the oocyte ageing which has been identified as the most important factor affecting egg quality after ovulation. Very little is known about the molecular changes associated with the progress of oocyte ageing. The present study monitored the egg viability rates during post‐stripping oocyte ageing in African catfish Clarias gariepinus . In addition the mRNA abundance of selected genes were studied during the progress of oocyte ageing by real time quantitative PCR. To study how maternal transcripts influence egg quality, expression levels were correlated with egg hatching rates. The highest embryo survival and hatching rates (88% and 81%, respectively) were obtained from eggs that were fertilized immediately after stripping. Complete loss of egg viability occurred at 16 and 24 hr Post Stripping (HPS) when eggs were stored at 25°C and 4°C respectively. Under both storage temperatures, the embryo mortality and larval malformation rates increased significantly over time and were the highest in the most aged oocytes. Genes indicating an upward trend in expression during ova ageing were determined to be related to oxidative injury and the stress response ( hsp70 ), mitochondrial function ( calmodulin ), apoptosis ( cathepsin D ) and germ line speciation ( vasa and sox9a ). The results suggest that oxidative stress and mitochondrial dysfunction might be associated with post‐stripping ova ageing and the consequent induction of egg quality defects. The examined genes may be considered as candidate markers of egg quality associated with oocyte ageing in African catfish.